Perancangan Desain Sistem Inventori Tool Crib Pada Bengkel Mesin - Riki Handoko; Hamzah Syahbana Munthe (Prosiding, 2023)
Information management for inventory is very important to help companies or organizations manage their inventory more efficiently and effectively. With good information management, companies can monitor and control the quantity of goods available, avoid shortages or excess stocks, and optimize the process of sending and receiving goods. The equipment management system in the POLMED Mechanical Engineering Workshop Tool Crib is still conventional, not yet using a technology-based (computer) management system. Where equipment borrowed by students or other stakeholders is still recorded in a form and there is no information management-based recording. So that the number of tools, the condition of the tools and who borrows the tools cannot be controlled properly. And problems/issues arise when the equipment is often not in place or missing.